Filling two needs with one deed: a combinatory mucosal vaccine against influenza A virus and respiratory syncytial virus - Vieira Antão, Ana; Oltmanns, Friederike; Schmidt, Anna; Viherlehto, Vera; Irrgang, Pascal; Rameix-Welti, Marie-Anne; Bayer, Wibke; Lapuente, Dennis; Tenbusch, Matthias (Frontiers in Immunology, 2024)
Influenza A Virus (IAV) and Respiratory Syncytial Virus (RSV) are both responsible for millions of severe respiratory tract infections every year worldwide. Effective vaccines able to preventing transmission and severe disease, are important measures to reduce the burden for the global health system. Despite the strong systemic immune responses induced upon current parental immunizations, this vaccination strategy fails to promote a robust mucosal immune response. Since intramuscular parental immunizations only induce very limited local immune responsesinduce strong systemic immune responses, but inefficiently induce mucosal immunity,Here, we investigated the immunogenicity and efficacy of a mucosal adenoviral vector vaccine to tackle both pathogens simultaneously at their entry site. For this purpose, BALB/c mice were immunized intranasally with adenoviral vectors (Ad) encoding the influenza-derived proteins, hemagglutinin (HA) and nucleoprotein (NP), in combination with an Ad encoding for the RSV fusion (F) protein. The mucosal combinatory vaccine induced neutralizing antibodies as well as local IgA responses against both viruses. Moreover, the vaccine elicited pulmonary CD8 + and CD4 + tissue resident memory T cells (TRM) against the immunodominant epitopes of RSV-F and IAV-NP. Furthermore, the addition of Ad-TGFβ or Ad-CCL17 as mucosal adjuvant significantly enhanced the formation of functional CD8 + TRM responses against the conserved IAV-NP. Consequently, the combinatory vaccine not only provided protection against subsequent infections with RSV, but also against heterosubtypic challenges with pH1N1 or H3N2 strains. In conclusion, we present here a potent combinatory vaccine for mucosal applications, which provides protection against two of the most relevant respiratory viruses.